2017
DOI: 10.1111/bcpt.12844
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Angiotensin‐Converting Enzyme Inhibitors are Associated with Reduced Mortality and Morbidity in Chronic Liver Disease

Abstract: Liver fibrosis is a common response to many chronic liver diseases. The aim of our study was to explore whether pharmacotherapy for concurrent diseases affects overall mortality, liver-related mortality and liver-related morbidity in patients with chronic liver disease. We performed a register-based cohort study of all patients with a first-time diagnosis of chronic liver disease between 2005 and 2012 in Sweden (n = 70 546). Data from the Patient Register, the Prescribed Drug Register and the Death Certificate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This was most notable among statin-naïve new initiators, the group most often studied in population-level cohorts of the effect of statins on survival in cirrhosis or chronic liver disease. 15,[17][18][19]45 We examined 2 distinct statin-exposed cohorts, existing users and new initiators, to assess the magnitude of decrease of mortality associated with each year of cumulative statin exposure, finding highly consistent effect sizes (HR 0.913-0.920) after adjusting for hyperlipidemia. These estimates suggest a much more modest impact of statin exposure than previous retrospective studies (HR 0.45 in meta-analysis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was most notable among statin-naïve new initiators, the group most often studied in population-level cohorts of the effect of statins on survival in cirrhosis or chronic liver disease. 15,[17][18][19]45 We examined 2 distinct statin-exposed cohorts, existing users and new initiators, to assess the magnitude of decrease of mortality associated with each year of cumulative statin exposure, finding highly consistent effect sizes (HR 0.913-0.920) after adjusting for hyperlipidemia. These estimates suggest a much more modest impact of statin exposure than previous retrospective studies (HR 0.45 in meta-analysis).…”
Section: Discussionmentioning
confidence: 99%
“…46 We postulate that the primary reasons for this difference include (1) adjustment for hyperlipidemia in our models and (2) treatment of statin exposure as a time-dependent covariate 47 rather than solely as a dichotomized variable with 28-to 90-day exposure windows as in previous studies. 15,[17][18][19] The use of dichotomized exposure variables cannot account for the impact of long-term cumulative statin exposure, which could decrease systemic inflammation and fibrosis. 47 A third potential reason for the smaller estimate of effect size in the present study is the use of comprehensive propensity matching using time-updated covariates, 48 which was highly effective in risk-set matching new initiators with non-initiators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with no hypertension included in the Group 3 showed the lowest mean fibrosis score supporting the theory that hypertension and activation of RAS contributes to fibrosis progression. Another registerbased cohort study of patients (n = 70,546) with a first-time diagnosis of chronic liver disease between 2005 and 2012 in Sweden revealed a marked reduction in liver-related mortality among patients with alcoholic liver disease who received ACE inhibitors [53].…”
Section: Ace Inhibitors (Acei) and Angiotensin II Type 1 Receptor Blomentioning
confidence: 99%
“…Statins are widely used in the treatment of hyperlipemia and coronary artery disease, which are also closely related to lipid metabolism, oxidative stress, and inflammation (Chen et al., ; Zheng et al., ). A recent study has reported that statins are associated with reduced total mortality among patients with ALD (Stokkeland et al., ). However, the underlying mechanism is unknown.…”
Section: Reversing Epigenetic Alterations For Ald Therapymentioning
confidence: 99%